SIKAP DAN STRATEGI K.H. AGUS SALIM TERHADAP IDEOLOGI KOMUNISME DI DALAM TUBUH SAREKAT ISLAM 1915-1926 - Yusuf Budi Prasetya Santosa (Tsaqofah, 2020)
This study aims to determine the attitudes and strategies of K.H. Agus Salim against the ideology of communism which was within the Sarekat Islam in 1915-1926. The method used in this research is a historical method and the presentation of the research results is done in a descriptive-narrative. The results of this study explain K.H. Agus Salim who disagreed with the entry of communist ideology into the Sarekat Islam. The ideology of communism brought by Heenk Sneevliet to Indonesia, and by Semaoen to the Semarang branch of the Sarekat Islam, is considered to be able to organize Sarekat Islam and divide Muslims. K.H. Agus Salim carried out various strategies so that the communist ideology that was already in the Sarekat Islam could be eliminated. Various strategies were also carried out to thwart the development of communist ideology among members of the Sarekat Islam in particular, and Muslims in general.